CITRA MEREK DAN PREFERENSI KONSUMEN DALAM PEMBELIAN PONSEL CERDAS KELAS MENENGAH BAWAH DI TOKO DARING INDONESIA - Fibrianto, Ary; Juhari, Juhari; Zufriady, Zufriady (LP2M Universitas Bina Bangsa, 2024)
The Samsung smartphone brand holds a positive image in the minds of Indonesian people. For years, Samsung has consistently been the market leader in Indonesia for smartphone sales using the Android software platform. This study aims to reinforce the findings of previous research, which used a quantitative descriptive approach, by re-examining one of its variables, namely brand image, using a non-interactive qualitative approach. The research was conducted by observing consumer preferences in purchasing decisions for four series of mid-to-lower-end smartphones with similar specifications but different brands, produced in the same year, on three of the most frequently accessed online stores by Indonesian consumers: Shopee, Tokopedia, and Bibli. The observation was carried out non-participantly on online sales data throughout 2023. It was complemented by interview results substituted with product reviews containing the strengths and weaknesses of a product from several accounts or gadget reviewer YouTube channels. The results of this study conclude that the brand image of Samsung, through a qualitative approach, also influences consumer preferences in making smartphone purchasing decisions, thus reinforcing the findings of previous research using quantitative methods